Yearbook Dutch Design 03/04 - Krol, Aad; VIVID Design and Premsela Dutch Design Foundation; de Rijk, Timo (Rotterdam : episode publishers, 2004)
This publication is based on an initiative and concept of VIVID Design, Rotterdam and Premsela Dutch Design Foundation, Amsterdam.
Adlib record nr. 530010539
Engels
boek
Keywords: 2003 - 2004